Coming Out Strategies on Social Media among Young Gay Men in Malaysia - Collin, Jerome; Ahmad Junaidi, Ahmad Hadzmy (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
Social media have afforded many young gay men the opportunity to explore their identities and practice coming out. The ease of use and the anonymity that can be assumed online has enabled young gay men to come up with different strategies of self-disclosure in social media. The present study seeks to examine these strategies among young gay men in Malaysia, given the limited data on the social media experiences of gay men in the country. In-depth interviews were conducted with six young, gay-identified men to find out the strategies they employed in disclosing their sexual identity online. The analysis of the interview data revealed that the coming-out strategies among the participants mostly resembled those employed by gay men in Western societies, including being out and proud, being out and discreet, and being closeted on social media. The analysis also revealed that the participants held different views regarding the role of social media in the coming out process for gay men in Malaysia. These findings have implications that are relevant to the issues of identity formation among gay men in contexts where homosexuality is still subject to social, legal, and religious condemnation.